Analysis of the Need for the Development of E-LKPD Biotechnology for Junior High Schools Based on the Local Wisdom of Subang Pineapple to Improve Understanding of Concepts and Creativity - Hamdiyah Hamdiyah; Dyah Rini Indriyanti; Sudarmin Sudarmin; Novi Ratna Dewi (MASI Mandiri Edukasi, 2026)
Biotechnology learning in junior high schools still faces challenges, including limited interactive teaching materials, teacher-centered instruction, and inadequate laboratory facilities, which hinder students' conceptual understanding and creativity. This study aimed to analyze the need to develop an ethnoscience-based biotechnology E-LKPD integrated with Project-Based Learning (PjBL) using the local wisdom of Subang pineapple (Ananas comosus (L.) Merr.). The study employed a convergent mixed-methods design involving 58 ninth-grade students and one science teacher at SMPN 2 Tambakdahan, selected through purposive sampling. Quantitative data were collected via Likert-scale questionnaires measuring understanding of the concept, creativity, and the need for interactive teaching materials, while qualitative data were collected through semi-structured interviews. Data were analyzed using descriptive statistics and thematic analysis through triangulation. The results showed that interactive E-LKPD had never been used (0%), while the need for digital teaching materials reached 95%, local wisdom integration 92%, and PjBL-based creativity features 96%. Students' initial scores of conceptual understanding and creativity were also relatively low. The study highlights the novelty of integrating ethnoscience and local wisdom into biotechnology E-LKPD as a contextual learning innovation and an alternative